Absenteeism And Beyond : Instructional Time Loss And Consequences - Abadzi, Helen (The World Bank, 2007)
Studies have shown that learning outcomes are related to the amount of time students engage in learning tasks. However, visits to schools have revealed that students are often taught for only a fraction of the intended time, particularly in lower-income countries. Losses are due to informal school closures, teacher absenteeism, delays, early departures, and sub-optimal use of time in the classroom. A study was undertaken to develop an efficient methodology for measuring instructional time loss. Thus, instructional time use was measured in sampled schools in Tunisia, Morocco, Ghana, and the Brazilian state of Pernambuco. The percentage of time that students were engaged in learning vis-à-vis government expectations was approximately 39 percent in Ghana, 63 percent in Pernambuco, 71 percent in Morocco, and 78 percent in Tunisia. Instructional time use is a mediator variable that is challenging to measure, so it often escapes scrutiny. Research suggests that merely financing the ingredients of instruction is not enough to produce learning outcomes; students must also get sufficient time to process the information. The quantity-quality tradeoff that often accompanies large-scale enrollments may be partly due to instructional time restrictions. Time wastage also distorts budgetary outlays and teacher salary rates. To achieve the Millennium Development Goals students must get more of the time that governments, donors, and parents pay for